Associations Between Smoking and Primary Sjögren Syndrome Classification Using the Sjögren's International Collaborative Clinical Alliance Cohort. Issue 3 (9th December 2021) - Gebreegziabher, Elisabeth A.; Oldenburg, Catherine E.; Shiboski, Stephen C.; Baer, Alan N.; Jordan, Richard C.; Rose‐Nussbaumer, Jennifer R.; Bunya, Vatinee Y.; Akpek, Esen K.; Criswell, Lindsey A.; Shiboski, Caroline H.; Lietman, Thomas M.; Gonzales, John A.
Abstract : Objective: The objective of this study was to examine the association of smoking with Primary Sjögren syndrome (pSS) classification and pSS diagnostic test results. We hypothesized that past and current smokers would have lower odds of being classified as having Sjögren syndrome (SS) and lower odds of having abnormal individual SS diagnostic test results compared with nonsmokers. Methods: Participants with suspected or established pSS were enrolled into the Sjögren's International Collaborative Clinical Alliance (SICCA) registry and had oral, ocular, and rheumatologic examinations performed; blood and saliva samples collected; and labial salivary gland biopsy examinations performed; they also completed questionnaires at baseline. Logistic regression was used to determine whether smoking status was associated with pSS classification and individual pSS diagnostic test results. Results: A total of 3514 participants were enrolled in SICCA. A total of 1541 (52.9%) met classification criteria for pSS. Compared with never smokers, current smokers had reduced odds of being classified as having pSS, reduced odds of having a focus score ≥ 1 and serologic positivity for anti‐SSA/anti‐SSB antibodies, and lower odds of having abnormal signs or test results of dry eye disease. Compared with never smokers, past smokers did not have a statistically significant reduction in odds of being classified as having pSS and of having abnormal individual pSS diagnostic test results. Conclusion: Compared with never smokers, current smokers in the SICCA cohort had lower odds of being classified as having pSS, lower odds of exhibiting abnormal signs and test results for dry eye disease, and lower odds of having a labial salivary gland biopsy supportive of pSS classification. Such negative associations, however, do not suggest that current smoking is of any benefit with respect to pSS.